On the Relationship between Speaking Anxiety, Academic Well-being, and Speaking Performance among Iraqi High School EFL Students - Ahmed R. azzawi (مجلة الباحث, 2026)
This study explored the complex relationships between speaking anxiety, academic well-being, and speaking performance in Iraqi EFL learners. Researchers collected data from 175 intermediate-level students using the Foreign Language Classroom Anxiety Scale (FLCAS) and measures of academic well-being. The analysis revealed important connections among these factors. The results showed a strong negative relationship between speaking anxiety and speaking performance, meaning that higher levels of anxiety significantly harmed the students' speaking abilities (with a correlation of r = -0.796, p < 0.01). There was also a notable negative link between speaking anxiety and overall academic well-being, suggesting that anxiety affected not only language tasks but also the students' broader psychological health (r = -0.549, p < 0.01). Additionally, when looking at different aspects of academic well-being, the students expressed a high value for school and satisfaction with their educational choices, but they also experienced considerable school burnout, creating a confusing situation in their educational experience. The study concluded that addressing mental health factors was essential for effective language teaching. It recommended that teachers implement strategies to reduce anxiety and foster supportive learning environments, balancing academic demands with psychological support to improve both language performance and student well-being